Refugees in the IT Sector: Young Syrians' Economic Subjectivities and Familial Lives in Jordan. - Pascucci, Elisa (Geographical Review, 2019)
This article explores refugee economic subjectivity in the context of restrictive asylum policies and disrupted transnational family lives. Drawing on fieldwork with young Syrian refugees pursuing IT training in Jordan, I focus on the "coding boot camp," an emerging educational format in the field of refugee professional training. I thus explore how Syrian youths approach humanitarian policies in which, in the absence of full social and economic rights for refugees, the question of livelihoods is addressed through the paradigms of self‐reliance, creativity, and innovation. Reframing the refugee from a "protected" to a "productive" subject, and offering individual solutions to a structural economic impasse, these policies produce tensions between individual responsibilities and more‐than‐individual relations and identifications—with families, religious identities, and national communities—that remain unresolved. The findings contribute to geographical scholarship on economic subjectivity, familial relations, and the migrant and refugee condition, while shedding light on some of the effects of the encounter between technology‐centred, neoliberal approaches to humanitarianism and restrictive migration regimes in responses to the Syrian displacement.